Kontribusi Mahasiswa dalam Mengenalkan Budaya Indonesia pada Anak melalui Tari Tokecang di TK Negeri Pembina Wirogunan, Kartasura - Nurul Ilmi Azizah, Annafi; Patma Uut Eka Saputri, Erlita; Khairurizky, Fatiha; Putri Maharani, Sahara; Alyaa, Sekar (Seulanga: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this community service explore the crucial role of students from UIN Raden Mas Said Surakarta in the effort to introduce and preserve dance culture in the modern era. The main focus of the service is to encourage students' understanding as agents of change who can effectively play their role in maintaining the sustainability and relevance of dance culture amid the dynamic challenges of the digital era. The community service activity in this article provides Tokecang Dance training for children which was held for 2 days at TK Negeri Pembina Kartasura, Sukoharjo. The service procedure used includes preparation, analysis of dance training design, implementation, and evaluation. As a result, students were able to practice traditional tokecang dance after attending the training, students were able to perform traditional tokecang dance at the dance art event held on Friday, May 18, 2024